Jane Allen, Center - Bancroft, Edith (Salt Lake City, UT : Project Gutenberg, 2012)
"Jane Allen: Center" by Edith Bancroft is a coming-of-age novel likely written in the early 20th century. The story centers around the character Jane Allen, a young girl preparing to leave her cherished ranch in Montana to embark on her junior year at Wellington College. The narrative explores her thoughts and feelings about leaving home, the friendships she forms, and the expectations of her college life. At the start of the story, Jane reflects on the changes in her life, anticipating her return to college while grappling with her emotions about leaving her father and Aunt Mary. As a light summer rain begins to fall, she excitedly interacts with her family, showcasing a lively and optimistic personality. The opening introduces various characters in Jane's life, including her Uncle Todd and Aunt Mary, setting the scene for Jane's hopeful yet uncertain journey ahead. As she receives a letter announcing that a scholarship she is involved with has been awarded to a Polish artist, the stage is set for her to navigate the complex dynamics of college life, new friendships, and possible challenges she may face upon her return. (This is an automatically generated summary.)
Release date is 2012-10-01
Roger Frank and the Online Distributed Proofreading Team
Keywords: College students -- Juvenile fiction; Young women -- Juvenile fiction; Women college students -- Juvenile fiction; Basketball stories